ANALISIS TOTAL FAKTOR PRODUKTIVITAS INDUSTRI MANUFAKTUR DI JAWA BARAT (2010-2015) - Rengganik, Rengganik; Sugiyono, Sugiyono (Universitas Mercu Buana, 2021)
Abstract. The objective of the research is to analyse an effect of labor, capital and raw material to output on medium and large scale of manufacturing industry in West Java during 2010-2015. This research used the analysis of quantitative method. The Root test, Cointegration test, Common Effect Model, Fixed Effect Model, Chow Test, Random Effect Model, Hausman Test have been applied to the research. The model that has been choosed is that Fixed Effect Model approach. The result of panel data regression analysis in this research showed that the labor, capital and raw material have significant effect to industrial output. The t test shows that the significance value is 0.01, meaning that the variables of labor, capital and raw material partially have a significant effect to industrial output. Based on the result of the research it can be concluded that the labor, capital and raw material have a significant effect on output of the medium and large manufacturing industry in West Java during 2010-2015. The researchers suggest that the quality of labor needs to be improved through training, adjusting to the expertise required by the manufacturing industry. Related to industrial raw materials, the quality of domestic raw materials needs to be increased in order to be equivalent to imported raw materials. For Capital, credit quota is needed to be improved especially for industrial investment and industrial working capital.Abstrak. Tujuan penelitian ini adalah mengkaji apakah terdapat pengaruh positif antara tenaga kerja, modal dan bahan baku dengan output industri manufaktur/pengolahan besar dan sedang di Jawa Barat periode 2010-2015. Pada penelitian ini, metode yang digunakan adalah analisis kuantitatif. Metode yang telah diujikan pada penelitian ini meliputi Uji Root, Uji Konitegrasi, Common Effect Model, Fixed Effect Model, Uji Chow, Random Effect Model, Uji Hausman. Fixed Effect Model menjadi model yang terpilih pada penelitian ini. Hasil regresi data panel menunjukan tenaga kerja, modal dan bahan baku memiliki pengaruh signifikan terhadap output industri. Uji t menunjukan nilai signifikansi sebesar 0,01 yang berarti secara parsial tenaga kerja, modal, bahan baku memiliki pengaruh signifikan pada output industri. Berdasarkan hasil penelitian dapat disimpulkan bahwa tenaga kerja, modal dan bahan baku memiliki pengaruh signifikan pada output industri manufaktur Jawa Barat 2010-2015. Peneliti menyarankan agar kualitas tenaga kerja perlu ditingkatkan melalui pelatihan, menyesuaikan dengan keahlian yang diperlukan oleh industri manufaktur. Terkait bahan baku industri, agar kualitas bahan baku dalam negeri ditingkatkan guna setara dengan bahan baku impor. Sementara pada modal, diperlukan peningkatan kuota kredit untuk investasi industri dan modal kerja industri.